Synthesis of pregnane 3-carboxylic acids via Pd-catalyzed alkoxycarbonylation and their effect on NMDA receptor activity - Šťastná, Eva; Chodounská, Hana; Pouzar, Vladimír; Borovská, Jiřina; Vyklický, Ladislav (Collection of Czechoslovak Chemical Communications, 2011)
We have prepared 20-oxo-5α- and 20-oxo-5β-pregnane-3-carboxylic acids by palladium catalyzed alkoxycarbonylation using triflate and nonaflate as the leaving groups in this substitution reaction. The activity of the synthesized compounds was studied in cultured rat hippocampal neurons under voltage-clamp conditions. The 5β-carboxylic acid derivatives were found to diminish NMDA-induced responses, whereas the 5α-derivative potentiated the response.
Keywords: Chemistry, Clinical; Steroids; kyseliny karbocyklické; Neurotransmitter Agents; neurotransmiterové látky; steroidy; klinická chemie; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; Acids, Carbocyclic